Effect of acrylonitrile–butadiene–styrene terpolymer on the foaming behavior of polypropylene. Issue 3 (May 2019) - Tan, Xiao-Tian; Zhou, Ying-Guo; Zhou, Jing-Jing; Dong, Bin-Bin; Liu, Chun-Tai; Xu, Bai-Ping
To improve the cellular foam structure of common polypropylene (PP), acrylonitrile–butadiene–styrene terpolymer (ABS) and compatibilizer were used to blend with PP, and the foaming behavior of PP/ABS blends was investigated. The solid and foamed samples of the PP/ABS blend with different component were first fabricated by melt extrusion followed by conventional injection molding with or without a blowing agent. The mechanical properties, thermal features, and rheological characterizations of these samples were studied using the tensile test, dynamic mechanical analyzer, differential scanning calorimetry, scanning electron microscopy, X-ray diffraction, and torque rheometry. The results suggest that ABS is a suitable candidate to improve the foamability of PP. The effect of ABS and compatibilizer on the foamability of PP can be attributed to three possible mechanisms, that is, the weak interaction between phases that facilitates cell nucleation, the improved gas-melt viscosity that prevents the escape of gas, and the influence of crystallization behavior that helps to form a fine foaming structure.